ENHANCEMENT OF PRIMARY CARE ASSESSMENT TOOL (PCAT): A SCOPING REVIEW - Ningsih, Dewi Surya; Surjoputro, Antono; Budi, Syamsulhuda (Universitas Airlangga, 2024)
Background: Strengthening the quality of primary health care is one way to improve public health. For this reason, an appropriate primary care assessment tool (PCAT) is necessary to evaluate and improve primary health care. Objective: This study aims to provide an overview of the development of primary care assessment tools. Methods: The study was conducted through a scoping review of articles written in English that were published in the PubMed, Scopus, Science Direct, and Semantic Scholar databases from 2010 to 2023. Results: A total of 10 selected articles describe the development of primary care assessment tools, namely PCAT Malawi, Vietnam PCAT-PE, Vietnam PCAT-AE, CR-PCAT (China), PCAT-TI (Tibet), UG-PCAT (Uganda), PCAT-C (China), PCAT-Facility (Spain), KS-PCAT (Standard Korean), PCAT-10 (Spain), and Colombia PCAT. Each tool has a different development focus according to the context of each country. Conclusion: This study provides an overview of the development of PCAT. In general, the development of PCAT in each country demonstrates different characteristics. The selection of a health service assessment tool must align with the needs of the element or aspect to develop. Keywords: primary care assessment tool, PCAT development, primary health care assessment, PCAT modification.